A comparative study of the historical and current development of the GCC insurance and takaful industry. Issue 2 (11th June 2018) - Alshammari, Ahmad Alrazni; Syed Jaafar Alhabshi, Syed Musa; Saiti, Buerhan
Abstract : Purpose: This paper aims to present a comparative examination of the historical and current profiles of the insurance and takaful industry in the Gulf region. Meanwhile, it will provide overview and insightful information of Gulf Cooperation Council (GCC) countries for insurance and takaful providers for their marketing strategy purpose. Design/methodology/approach: This paper uses insurance and takaful sectors in Gulf region as an exploring area where the data are extracted from the regulators' annual reports and other reports issued by research houses and market players, e.g. Islamic Financial Services Industry, Swiss Re and Milliman. Findings: The comparative analysis reveals that insurance activities penetrated the Gulf region through foreign institutions. After independence and booming oil prices, local institutions established the industry in an unregulated environment. As the industry grew and matured, the sector gradually became regulated. This supported the growth of the industry, leading to the emergence of the biggest takaful market in the world, with 72 takaful operators. Almost half of the takaful operators operate in the Saudi market. Regarding business lines, general lines dominated because of compulsory motor insurance for all cars and health insurance for expatriates. Insurance penetration and insurance density recorded a low figure in GCC compared to the global market because of a lack of product development, especially in family line, which many people think the life insurance contradicts Islamic law. Furthermore, it is low due to the poor channel of distributions with depend heavily on insurance agents that fails to reach the customers. Research limitations/implications: Interestingly, the takaful market share is considered very low, e.g. 9 per cent in Oman 9 and 9.2 per cent in UAE, where the majority of population is Muslim, indicating that takaful providers should focus in these countries to grab better market shares. Originality/value: As takaful business is an emerging area in Islamic finance and many insurance players are interested in it, this paper provides an overview and marketing insights of insurance and takaful industries in the GCC region.